Management of financial institutions in Africa: Emerging themes and future research agenda. (3rd July 2019) - Adeleye, Ifedapo; Debrah, Yaw A.; Nachum, Lilac
ABSTRACT: The rise of the financial services sector in Africa over the last decade or so has been phenomenal, marked by significant advances in mobile money, and growing financial inclusion and profitability. However, there are significant gaps in the academic literature on the sector, as most recent studies have focused on the more technical aspects of economics, banking and finance, with little attention paid to the management of financial institutions, and the strategic behavior of financial services players. This special issue attempts to fill these gaps. In this introductory paper, we provide an overview of three important trends or thematic areas that the papers in the special issue address: the decline of foreign banks in Africa; the rise of pan-African banks; and how frugal innovation and fintech are shaping the future of financial services in Africa. We also outline three avenues for future research: historical perspectives on financial services; indigenous financial institutions; and mergers, acquisitions and strategic alliances.